Patterns of red‐cell transfusion use in obstetric practice in sweden 2003‐2017: A nationwide study. Issue 7 (2nd February 2021) - Brynolf, Anne; Zhao, Jingcheng; Wikman, Agneta; Öberg, Sara; Sandström, Anna; Edgren, Gustaf
Abstract: Background: There is a paucity of data on patterns of red‐cell transfusions in obstetrical care, but some studies have suggested an increase in transfusion rates during the last decade. The purpose of this study was to investigate maternal characteristics, temporal trends and hospital variations in red‐cell use in a large contemporary obstetric cohort in Sweden. Study design and methods: Nationwide observational cohort study of maternal red‐cell transfusions for all deliveries in Sweden between 2003 and 2017. Results: The proportion of deliveries that received red‐cell transfusions was stable during the study period, although the number of red‐cell units administered per delivery declined. Among transfused women, most received a low‐volume transfusion of 1 or 2 units. Red‐cell transfusion was more common among the nulliparous, for instrumental and caesarean deliveries, and with increased maternal age. We saw large variations in transfusion rates between hospitals in Sweden, despite adjusting for age and parity. Conclusions: In comparison to other high‐resource countries we see a high proportion of deliveries with maternal red‐cell transfusions. However, we do not see an increase in red‐cell use over time.